Experimental Demonstration of the Distributed Feedback Semiconductor Laser With S-Bent Waveguide and Sampled Grating - Yunshan Zhang; Yuechun Shi; Lianyan Li; Zhengpeng Zou; Jun Lu; Yinchao Du; Wenxuan Wang; Yating Zhou; Xin Chen; Jilin Zheng; Xiangfei Chen (IEEE Photonics Journal)
A distributed feedback (DFB) semiconductor laser based on s-bent waveguide and sampled grating is theoretically studied and experimentally demonstrated. The proposed laser operates with a high side mode suppression ratio (SMSR) when the bias current is changed from 50 to 130 mA. When the bias current is fixed at 130 mA, the SMSR is larger than 55 dB, which is benefit from the suppressed spatial hole burning, while the SMSR of the equivalent phase shifted DFB laser decreases to 39 dB. The wavelength spacing error between two proposed DFB lasers is measured to be 0.089 nm compared with the designed value. When temperature is increased from 20 °C to 42 °C, the presented DFB laser achieves stable single longitudinal mode (SLM) operation with SMSR >51 dB and the wavelength varies from 1562.24 to 1564.6 nm with a slope of 0.11 nm/°C. The s-bent waveguide and sampled grating can be fabricated simply by the common holography exposure and photolithograph technique resulting in a low cost. Besides, the wavelength accuracy and SLM yield can be improved significantly, which is very beneficial for the multiwavelength DFB laser array.